Exploring the initiation of fiber fuse - Qirong Xiao (Nature Portfolio, 2019)
Abstract We report an investigation of conditions for the initiation of fiber fuse (IFF), a kind of catastrophic damage that troubles all kinds of optical fibers, in silica-based optical fibers. The fibers of different chemical compositions were processed and tested in controlled conditions without mechanical damages before the IFF. For all the fibers of IFF, the same correlation between the critical temperatures and the optical powers transmitted therein was revealed for the first time. The fibers of different chemical compositions exhibited different resistances to the IFF under the threshold powers for propagation of fiber fuses. The results offered promise for predicting fiber fuses in optical fiber systems, which could facilitate avoiding catastrophic losses. They could direct the optimization of fiber production technologies for suppressing the damages, as well as open a new path towards controlled utilization of fiber fuse in in-fiber microstructure fabrication.